ST electronic (training & simulation systems) tech-factor challenge 2013/2014 (2) : autonomous casualty extraction robot with avatar control - Wang, Jingyuan (2014)
ST Electronic has organized a university-level robotic competition “Tech-Factor Challenge 2013/14” for final-year students from NTU and NUS. The topic is to design and develop robotic application ideas for military/security/civil defence use involving the robot making decisions and taking actions to complete a task, and build a related demonstrable robotic prototype. In order to participate in this competition, the author and his teammate have built a robot all the way from scratch to a workable prototype through their final-year study period. The robot developed can perform rescue, transport and surveillance tasks in the military or civil defence environment. During the development period, the author is mainly deal with the hardware and mechanical problems involved. This report will cover the process of developing suitable solutions and author’s learning in the hardware and mechanical development. Compared to software development, hardware and mechanical developments are focus more on the practices at the practical level instead of theoretical level. This report will mainly focus on hands-on construction experiences and some support theories in the process of solving some electrical control problems. As an Information Engineering & Media student, the author was mainly trained in solving software and information communication problems in his earlier undergraduate study. This competition gave the author a great opportunity to solve engineering problems from a totally different perspective. A learning & discussion session will be covered at the end of this report. The author believe this report will be beneficial for people who have trained in solving problems in theory level and want to make them prepared to solve problems from a practical approach.